ANALISIS MISKONSEPSI PESERTA DIDIK MENGGUNAKAN THREE DIAGNOSTIC TEST PADA MATERI BILANGAN BERPANGKAT DI KELAS IX MTS NURUL HASANI - Widya, Widyanti (UNIVERSITAS TANJUNGPURA, 2025)
The purpose of this study is to identify the misconceptions of studen questions about power numbers and causative factors in class IXB MTs Nurul Hasani Teluk Batang. The method used in this research is a descriptive method in the form of case study research. Subject the research is as many as 15 students of class IXB MTS Nurul Hasani Teluk Batang. The instrument used in this research is a three-tier diagnostic Test and interview guidelines. Based on the result of the research carried out obtained by students who experienced the misconception of specialization as much as 10 students or 45% of 22 students and misconceptions generalization of 5 students or 23% of 22 students. The cause of the misconception of the students in this study is reasoning or wrong/ incomplete reasoning and students' ability. Keywords: Misconception, Three-tier Diagnostic Test, Numerical Material Ranked